2007
DOI: 10.1029/2006jb004301
|View full text |Cite
|
Sign up to set email alerts
|

Olivine friction at the base of oceanic seismogenic zones

Abstract: [1] We investigate the strength and frictional behavior of olivine aggregates at temperatures and effective confining pressures similar to those at the base of the seismogenic zone on a typical ridge transform fault. Triaxial compression tests were conducted on dry olivine powder (grain size 60 mm) at effective confining pressures between 50 and 300 MPa (using Argon as a pore fluid), temperatures between 600°C and 1000°C, and axial displacement rates from 0.06 to 60 mm/s (axial strain rates from 3 Â 10 À6 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
172
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(189 citation statements)
references
References 48 publications
17
172
0
Order By: Relevance
“…A temperature of 600 • C likely represents the lower base of the seismogenic zone for the oceanic lithosphere, as seismological studies found that the occurrence of earthquakes in the oceanic lithosphere appear to be limited in depth range by the 600 • C isotherm Ekström, 2001, 2003;McKenzie et al, 2005). Consistently, evidence from naturally and experimentally deformed peridotite was presented that the transition from brittle to plastic deformation occurs at about 600 • C (e.g., Jaroslow et al, 1996;Warren and Hirth, 2006;Boettcher et al, 2007;Druiventak et al, 2011). Depending on the pair of activation enthalpies used, significant transformation will occur after tens to hundreds of years or it may last up to ten thousands of years until volume fractions of detectable size have undergone this specific microstructural transformation.…”
Section: Extrapolation To Natural Conditionsmentioning
confidence: 51%
“…A temperature of 600 • C likely represents the lower base of the seismogenic zone for the oceanic lithosphere, as seismological studies found that the occurrence of earthquakes in the oceanic lithosphere appear to be limited in depth range by the 600 • C isotherm Ekström, 2001, 2003;McKenzie et al, 2005). Consistently, evidence from naturally and experimentally deformed peridotite was presented that the transition from brittle to plastic deformation occurs at about 600 • C (e.g., Jaroslow et al, 1996;Warren and Hirth, 2006;Boettcher et al, 2007;Druiventak et al, 2011). Depending on the pair of activation enthalpies used, significant transformation will occur after tens to hundreds of years or it may last up to ten thousands of years until volume fractions of detectable size have undergone this specific microstructural transformation.…”
Section: Extrapolation To Natural Conditionsmentioning
confidence: 51%
“…Mafic rocks are brittle to greater temperatures, with a brittle -viscous transition in olivine at temperatures in excess of 650-700 8C (Karato & Wu 1993;Passchier & Trouw 2005). Boettcher et al (2007) observed a change from velocityweakening to velocity-strengthening behaviour of olivine in laboratory friction experiments, and extrapolated the temperature dependence of this transition to approximately 600 8C at geological strain rates. They interpret the physical reasoning for this transition in frictional stability to be the onset of dislocation glide, allowing for asperity deformation and slip-hardening (Boettcher et al 2007).…”
Section: Dislocation Creepmentioning
confidence: 99%
“…Boettcher et al (2007) observed a change from velocityweakening to velocity-strengthening behaviour of olivine in laboratory friction experiments, and extrapolated the temperature dependence of this transition to approximately 600 8C at geological strain rates. They interpret the physical reasoning for this transition in frictional stability to be the onset of dislocation glide, allowing for asperity deformation and slip-hardening (Boettcher et al 2007). Thus, if dislocation creep is the major viscous deformation mechanism in the mid-to lower crust, thermal structure and mineralogy determine the maximum depth of frictional failure and unstable frictional behaviour, possibly also constraining the depth of the seismogenic zone (Scholz 1988).…”
Section: Dislocation Creepmentioning
confidence: 99%
“…Laboratory studies show that the rate-state friction laws are applicable to high-temperature lower crust conditions [Blanpied et al, 1995;Boettcher et al, 2007]. The rate-state friction parameters can been related to microscale ductile deformation processes [e.g., Boettcher et al, 2007;Rice et al, 2001].…”
Section: Transient Creep Modelmentioning
confidence: 99%